Му-му. Змея и чаша: Роман / А. Н. Воронин - Воронин А. Н. (Современный литератор, 2002)
Экземпляры: ф.12 (2003) / Инвентарный номер: 47588 / Цена: / Сис.шифр: 84(2Рос=Рус)6-44 / Авт.знак: В75 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44